The relationship between lower extremity alignment and Medial Tibial Stress Syndrome among non-professional athletes - Raissi , G. R. D.; Cherati, A. D. S.; Mansoori, K. D.; Razi, M. D. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2009)
Objective To determine the relationship between lower extremity alignment and MTSS amongst non-professional athletes